Oral manifestations in crohn’s disease patients (scoping review) - Chamilia Chantika, Alya; Nova Fitri, Andrian (Fakultas Kedokteran Gigi Universitas Trisakti, 2024)
Background: Crohn's disease is an autoimmune disease that can affect all parts of the digestive tract, from the mouth to the anus. Manifestations of Crohn's disease are found in the liver, skin, joints, eyes, bile ducts, and the oral cavity. Up to 60% of cases found, oral manifestation occurred before the gastrointestinal tract is involved. Purpose: The aim of this study is to determine the oral manifestations found in Crohn’s disease patients. Method: This is an observational descriptive study with a scoping review method using the PRISMA diagram as a guideline. There are four electronic databases used for data collection which are, PubMed, Wiley Online Library, Unbound MEDLINE, and TripDatabase. Results: From this study, there are 18 types of oral manifestations found in Crohn's disease patients which are lip swelling (66,6%), aphthous stomatitis/mouth ulcer (55,5%), angular cheilitis (38,8%), gingival manifestations (38,8%), cobblestone (27,7%), periodontal disease (11,1%), redness of the soft palate (5,5%), plaques of pink papules in the posterior buccal mucosa and retromolar pad (5,5%), ulceration on the uvula, pillars of fauces and posterior pharyngeal wall (5,5%), hyperplasia palatal mucosa (5,5%), caries (5,5%), mucosal tag (5,5%), perioral edema (5,5%), perioral erythema (5,5%), apical periodontitis (5,5%), recurrent tonsillitis (5,5%), and enamel hypoplasia (5,5%). Conclusion: The four most common oral manifestations in Crohn’s disease are lip swelling, aphthous stomatitis, angular cheilitis, and gingival manifestations.